1997
DOI: 10.1038/sj.ijo.0800494
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of dietary fat by sucrose or starch: Effects on 14 d ad libitum energy intake, energy expenditure and body weight in formerly obese and never-obese subjects

Abstract: OBJECTIVE: To investigate the impact of a high-sucrose diet vs a high-starch and a high-fat diet on 14 d ad libitum energy intake, body weight, energy expenditure and sympathoadrenal activity. MEASURMENTS: Food intake; body weight and composition (bioelectrical impedance); 24 h energy expenditure, substrate oxidation rates, spontaneous physical activity, heart rate and appetite sensations in a respiration chamber (VAS scores); plasma catecholamine concentration and blood pressure. SUBJECTS: Twenty normal-weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
1
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 23 publications
6
82
1
2
Order By: Relevance
“…13±18 In a longer-term study over 14 days, Raben et al described increased carbohydrate oxidation and suppressed fat oxidation following 14 day controlled ad libitum intake of a sucrose-rich diet (23 E% sucrose) as compared to a starchrich diet (2 E% sucrose). 19 However, in that study energy intake was higher on the sucrose-rich diet compared with the starch-rich diet, which may explain the higher RQnp on the sucrose-rich diet.…”
Section: Carbohydrate and Substrate Utilisation Th Vasilaras Et Alcontrasting
confidence: 45%
See 1 more Smart Citation
“…13±18 In a longer-term study over 14 days, Raben et al described increased carbohydrate oxidation and suppressed fat oxidation following 14 day controlled ad libitum intake of a sucrose-rich diet (23 E% sucrose) as compared to a starchrich diet (2 E% sucrose). 19 However, in that study energy intake was higher on the sucrose-rich diet compared with the starch-rich diet, which may explain the higher RQnp on the sucrose-rich diet.…”
Section: Carbohydrate and Substrate Utilisation Th Vasilaras Et Alcontrasting
confidence: 45%
“…In one longer-term study a higher 24 h energy expenditure was also seen after 14 days ad libitum intake of a sucrose-rich, low-fat diet compared to a starch-rich, low-fat diet. 19 However, this study was still not long enough to allow adaption to the diets and the effects may have been temporary.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies examining the effect of GI on EE have been performed with simple sugars (fructose compared to glucose) (Ritz et al, 1991;Raben et al, 1994Raben et al, , 1997Tagliabue et al, 1995), where increased TEF was observed with fructose, which has a lower GI compared to glucose. Significant differences in TEF and satiety with carbohydrate foods were observed by Raben et al (1994) who noted significantly lower TEF and increased fullness with high-fibre (4.7 g/MJ) compared to low-fibre (1.7 g/MJ) meals.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of consistency in the evidence on whether sugars and starches have similar effects on appetite and body weight. Raben et al (1997) found that a high-starch diet resulted in lower energy intakes and reductions in body weight after 14 d compared with a high-sucrose or high-fat diet. Lawton et al (1998) found that giving high carbohydrate sweet or high carbohydrate savoury snacks had similar effects on energy intake and body weight over 21 d.…”
Section: Metabolism Of Dietary Componentsmentioning
confidence: 94%